Strategy to Increase Accreditation of Special Education Schools Through Accelerating the Fulfillment of National Education Standards - Kadarisman, Kadarisman; Fatmasari, Rhini; Siswanto, Romi; Budi, Laksana (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The aim of this research is to determine the efforts and strategies carried out by SLB to meet national education standards in order to improve school accreditation. This research used a quantitative approach with a total of 234 respondents from 34 special schools in the Padang City and DI Yogyakarta areas who were selected using purposive sampling. The data source for this research is primary data with data collection techniques through filling out questionnaires and FGDs. The research data that has been collected is carried out through SPSS analysis. The research was conducted from February to October 2023. The results of the research show that management standards, financing standards, facilities and infrastructure standards as well as standards for educators and education personnel provide a positive and significant influence on strategies for increasing SLB accreditation, while content standards, process standards, standards graduate competencies and assessment standards do not have a positive and significant influence on strategies for increasing SLB accreditation. However, it is known that each educational standard is related to other educational standards, so it is necessary to carry out various standard optimizations so that each educational standard can be implemented optimally to obtain optimal accreditation results.